2019
DOI: 10.31387/oscm0380238
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Measurement of Relational Capital in Supply Chains

Abstract: The aim of the paper is to identify and systemise dimensions and measures that can be used to evaluate buyersupplier relational capital (RC). The authors used a literature review methodology composed of the following phases: question formulation, keyword search in databases, screening and analysis of articles. As a result, 44 articles were selected and finally analysed in detail. It was found that several theories can help to explain how buyer-supplier relationships contribute to a company's value and competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…, 2012; Still et al. , 2013; Hosseini and Owlia, 2016; Walecka and Zelek, 2017; Ocicka and Wieteska, 2019). The smallest common denominator seems to be that RC comprises external relationships of an organization.…”
Section: Literature-based Hypothesis Development and Variable Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2012; Still et al. , 2013; Hosseini and Owlia, 2016; Walecka and Zelek, 2017; Ocicka and Wieteska, 2019). The smallest common denominator seems to be that RC comprises external relationships of an organization.…”
Section: Literature-based Hypothesis Development and Variable Selectionmentioning
confidence: 99%
“…unclear. For example, several authors have compiled and discussed the multitude of RC definitions (Mart ın- de-Castro et al, 2011;Manzari et al, 2012;Still et al, 2013;Hosseini and Owlia, 2016;Walecka and Zelek, 2017;Ocicka and Wieteska, 2019). The smallest common denominator seems to be that RC comprises external relationships of an organization.…”
Section: Introductionmentioning
confidence: 99%
“…A strong, long-term cooperation can be seen as a foundation for establishing a beneficial relationship (Ocicka and Wieteska, 2019). Cooperation between supplier and buyer has also been impacted by digitalization, however the direction of impact (positive or negative) is determined by different contexts.…”
Section: Impact Of Digitalization On Processual Elements Of Bsrmentioning
confidence: 99%
“…Partners who interact closely can benefit from learning and sharing knowledge and expertise (Ocicka and Wieteska, 2019).…”
Section: Impact Of Digitalization On Processual Elements Of Bsrmentioning
confidence: 99%
“…Relational capital is also composed of all the resources linked to the firm's external relationships with customers, suppliers, and other partners (Mousavi & Takhtaei, 2012). The literature review conducted by Ocicka and Wieteska (2019) identified five components that are recurrently noted as relational capital attributes in supply networks: trust, close interaction, respect, reciprocity, and commitment.…”
Section: Social Capital Theorymentioning
confidence: 99%